Pendampingan UMKM Desa Kedongdong Kidul di Era Digital - Sulistyo Hadi; Hafni Khairunnisa; Afif, Fuadi; Abdul Holis (Jurnal Abdimas Pariwisata, 2025)
Assistance for MSMEs in Kedongdong Kidul Village in the Digital Era This community service activity aims to improve the understanding and skills of micro, small, and medium enterprises (MSMEs) in Kedongdong Kidul Village in utilizing digital technology, particularly in marketing and business management. The program was conducted through seminars and training sessions focusing on the use of social media and e-commerce platforms as digital marketing tools. Additionally, intensive mentoring was provided to assist MSMEs in implementing the digital technologies learned. The results indicated a significant improvement in participants' understanding of digital marketing, although challenges such as limited infrastructure and low digital literacy remain obstacles. To address these issues, further programs focused on enhancing digital literacy and improving technological infrastructure are recommended. This activity has made a significant contribution to supporting the development of digital-based MSMEs in rural areas, especially in the era of globalization and digital transformation..